Juristische Methodenlehre und Immobiliarsachenrecht Deutsch-chinesische Tagung vom 21.-23.8.2013 - Schubert, Claudia; Huang, Hui; Säcker, Franz Jürgen (Mohr Siebeck, 2015)
German legal methods have been received in China and adapted on an abstract level in the academic debate there. Its integration in the legal reasoning of cases and the legal analysis of statutes was the subject of a conference for Chinese and German scholars in August 2013. The legal argumentation concentrated on the law of immovable property, and especially home ownership, something which has caused significant legal conflicts in China. This volumes documents the Chinese-German dialogue on the subject.
PublicationDate: 20150225
Keywords: Vormerkung -- Eigentum -- Wohnungseigentum -- unbewegliche Sache -- dinglicher Erwerb -- Sicherungsrechte -- Ostasien -- Bürgerliches Recht -- Internationales Privatrecht